Climax: Biology and Ethics in Environmental Restoration - Neira-Barrera, H (Environmental Philosophy Inc, 2019)
Justifications for the environmental restoration of the Pumalín National Park, originally known as Pumalín Nature Sanctuary, in Chile can be analyzed from a philosophical and ethical point of view. The environmental stage to which the park should be restored is defined as a moral choice, rather than an ecological one, that is based on “climax” as an a priori value that supports and guides the main restoration actions carried out in the park. This climax is a pre-settling or pre-colonization condition. Defined philosophically, climax is both an ethical and political value. For these actions, the ecosystem s health can be treated the same as that of a human s health: each society defines the criteria and the acme of health, as well as the valid efforts to restore it. © 2019 Environmental Philosophy Inc. All rights reserved.